Independensi Hakim Konstitusi di Tengah Badai Polarisasi Politik: Penelitian - Selviana Teras Widy Rahayu; Afendra Eka Saputra; Agus Salim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Constitutional Court is one of the judicial authorities, alongside the Supreme Court, as stipulated in Article 24 paragraphs (1) and (2) of the 1945 Constitution of the Republic of Indonesia. However, a problem arises when the credibility of the Constitutional Court judges, who are supposed to ensure substantive justice, is tarnished by acts of corruption and irresponsibility. This raises questions about how to supervise them, as the interests and subjectivity of the judges can also be reflected in the decisions they make, which can ultimately lead to unfair and incorrect outcomes. Furthermore, the controversy surrounding Constitutional Court Decision Number 90/ PUU-XXI/2023 has sparked debate about the judges' bias in making decisions related to political interests. The expansion of authority without a credible and reliable oversight process and institution has proven to be problematic for the Constitutional Court, particularly with the establishment of the newly formed Honorary Council. This study employs a normative legal method, referencing applicable laws and regulations, cases, and concepts. The purpose of this study is to determine the independence of Constitutional Court judges amid political polarity and to examine the oversight of Constitutional Court judges, especially considering the final and binding nature of their decisions. Additionally, to date, the Constitutional Court does not have an external oversight body. We must not allow the decisions made to undermine the democratic order and provide room for intervention in the work of the Constitutional Court judges as guardians of the constitution.